Exploring the Perceptions of Radiologist Technicians on the Importance of Anatomical Knowledge in Improving the Quality of Radiographic Images: A Qualitative Study in Saudi Arabian Hospitals - Jawaher Fahat Obeid Alanzi, Hind Faisal Almoutiri, Ahlam Mohammed Alenazi, Khalid Zaben Alanazi, Eman Abdulaziz Alqureshi, Jawaher Ayied Almatrafy; Fatmah Mohammed Alanazi, Alhanouf Raed Alhussinan, Fahad Matar Rashid AL Mutairi, Mohammed Muraizeq Alotaibi (Journal of International Crisis and Risk Communication Research, 2024)
Background: Anatomical knowledge is crucial for radiologist technicians to produce high-quality radiographic images. However, the perceptions of radiologist technicians regarding the importance of anatomical knowledge in their practice have not been extensively explored in Saudi Arabia. This qualitative study aimed to investigate the perceptions of radiologist technicians on the significance of anatomical knowledge in improving the quality of radiographic images in Saudi Arabian hospitals. Methods: A qualitative research design was employed, involving semi-structured interviews with 20 radiologist technicians purposively sampled from various hospitals across Saudi Arabia. The interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Results: Four main themes emerged from the data analysis: (1) the perceived importance of anatomical knowledge, (2) the impact of anatomical knowledge on image quality, (3) challenges in acquiring and applying anatomical knowledge, and (4) strategies for enhancing anatomical knowledge. Participants emphasized the significance of anatomical knowledge in their practice and its direct influence on the quality of radiographic images. However, they also identified challenges, such as limited educational opportunities and time constraints. Suggested strategies for improvement included continuous education, hands-on training, and interprofessional collaboration. Conclusions: Radiologist technicians in Saudi Arabia perceive anatomical knowledge as essential for producing high-quality radiographic images. Addressing the challenges and implementing the suggested strategies can enhance the anatomical knowledge of radiologist technicians, ultimately improving the quality of radiographic images and patient care. The findings highlight the need for targeted educational interventions and support for radiologist technicians in Saudi Arabia.